La notion de famille et son impact en droit social - Castelli, Mireille (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
This paper surveys references to the family in social legislation, with more specific regard to social security schemes providing coverage to a broad section of the population. Such references are seen as involving two types of questions. First, do statutory references to the family invoke a definite concept of the family cell ? And second, in what ways do family relationships influence one's position under social security legislation ? Thus the first part of the paper is an attempt to elucidate the concept of the family underlying social security legislation. This is done by considering the legislative treatment of three components of family relationships, which seem to play, either separately or in conjunction, a particularly significant role in statutes of this type : the network of interpersonal relationships that are included in the family, the concept of dependency, and the consequences attributed to cohabitation. The second part of the paper surveys the impact of family relationships on rights and duties under social security legislation. This part opens with a broad description of social legislation generally, followed by a threefold classification of social security schemes according to the type of economic hazard against which compensation is provided: loss of income, lack of income, increase in needs. The impact of family relationships in each group of statutes is then brought under detailed analysis, and a number of anomalies are pointed out. The general picture disclosed by the paper is one of severe confusion, both as to the concept of the family itself and as to the impact of family relationships on social security benefits. While inconsistencies of the latter kind may be explained and justified in a number of cases, it seems desirable that a single concept of the family be adhered to in all social security statutes. This, however, should not preclude variations where warranted by the policy of the Act, general standards of morality, or the particular purpose sought by statutory reference to family relationships.